HELMET USE AMONG SKIERS AND SNOWBOARDERS IN SOUTHERN ALBERTA. Issue 7 (11th March 2014) - Pfister, K; Romanow, N; Emery, C; Meeuwisse, W; Nettel-Aguirre, A; Hagel, B
Abstract : Background: There is little information on ski/snowboard helmet prevalence at ski areas in southern Alberta, with no published reports on correct helmet fit or helmet standards. Objective: To determine the prevalence of helmet use and correct helmet fit among skiers/snowboarders at an Alberta ski area. Design: Cross-sectional survey. Setting: An urban ski area in Alberta, Canada. Participants: Skiers/snowboarders of all ages. Risk factor assessment: Skiers/snowboarders were interviewed (n=914) and systematically observed (n=2014) at the ski area. Main outcome measurements: Helmet use and correct helmet fit. Prevalence ratios (PR) with 95% confidence intervals (CI) were calculated for each outcome separately for interviews and systematic observations. Results: Preliminary results for helmet use indicate that the likelihood of wearing a helmet is higher for those <13 years old (PR 1.09; 95% CI 1.01–1.17) and for 13–17 year olds (PR 1.13; 95% CI 1.07–1.20) compared with older participants; skiing/snowboarding with adults (PR 1.24; 95% CI 1.11–1.40) vs. alone, and if adult companions were wearing a helmet (PR 3.01; 95% CI 1.71–5.30). Preliminary results for helmet fit indicate that the likelihood of wearing a helmet correctly increases if skiing/snowboarding with adults and children (PR 2.86; 95% CI 1.28–6.36) vs. no companions, and if the child was wearing a helmet (PR 4.45; 95%CI 1.22− 16.28). The likelihood of wearing a helmet correctly was lower for ages 13–17 (PR 0.80; 95% CI 0.69–0.93) compared with 18–54 and for snowboarders (PR 0.87; 95% CI 0.77–0.97) compared with skiers. Conclusions: This information has the potential to influence policy regarding mandatory helmet use and may be used to educate those with an interest in helmet safety and the public on the use and correct use of a helmet.